Children's embodied experience of living with domestic violence: "I'd go into my panic, and shake, really bad". Issue 4 (December 2016) - Callaghan, Jane; Alexander, Joanne; Fellin, Lisa
Abstract Children who experience domestic violence are often described in academic and professional literature as passive victims, whose 'exposure' to violence and abuse at home leaves them psychologically damaged, socially impaired, inarticulate, cognitively 'concrete' and emotionally 'incompetent'. Whilst we recognise the importance of understanding the hurt, disruption and damage that domestic violence can cause, we also explore alternative possible ways of talking about and thinking about the lives of children who have experienced domestic violence. We report on interviews and drawings with 27 UK children, using interpretive analysis to explore their capacity for agency and resistance. We explore the paradoxical interplay of children's acceptance and resistance to coercive control, paying specific attention to embodied experience and use of space. We consider how children articulate their experiences of pain and coercion, how they position themselves as embodied and affective subjects, and challenge Scarry's (The Body in Pain, OUP, Oxford, 1985) suggestion that embodied pain and violence are inexpressible.